Predictive factors in the treatment of streptococcal endophthalmitis - Yospaiboon Y (Dove Medical Press, 2018)
Yosanan Yospaiboon, Kidakarn Meethongkam, Suthasinee Sinawat, Wipada Laovirojjanakul, Tanapat Ratanapakorn, Thuss Sanguansak, Chavakij Bhoomibunchoo KKU Eye Center, Department of Ophthalmology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Objective: To evaluate visual outcomes and possible predictive factors in the treatment of infectious endophthalmitis caused by Streptococcus species during 2012–2016 at a large referral eye center in northeastern Thailand.Methods: A retrospective medical record chart review of patients with culture-positive endophthalmitis caused by Streptococcus species was conducted. Demographic data including age, gender, occupation, duration of symptoms, time to surgery, surgical procedures, initial visual acuity at presentation, and final visual acuity after treatment were collected and analyzed. Possible predictive factors associated with improved visual outcomes were also studied.Results: Forty-five eyes of 45 patients were recruited for the study. The 3 most common types of endophthalmitis were postoperative (35.56%), posttraumatic (20%), and endogenous (15.56%). At presentation, most patients (95.56%) had visual acuity of hand motion (55.56%), light perception (28.89%), or no light perception (11.11%). The 3 most common isolates were Streptococcus pneumoniae (44.44%), Group B β-hemolytic Streptococcus (26.68%), and Streptococcus viridans (20%). Most patients (62.22%) were treated with surgical interventions, either pars plana vitrectomy with intravitreal antibiotics or pars plana vitrectomy with intravitreal antibiotics and silicone oil tamponade. After treatment, improved visual outcome was noted in only 9 patients (20%), and no visual improvement was seen in 36 patients (80%). Evisceration and enucleation were performed in 15 patients (33.33%). The only possible predictive factor associated with improved visual outcomes was early vitrectomy, performed within 3 days.Conclusion: Streptococcal endophthalmitis is often associated with poor visual prognosis. Only 9 patients (20%) had improved vision after treatment. The only possible predictive factor associated with improved visual outcomes was vitrectomy within 3 days. Early diagnosis and early vitrectomy are therefore recommended. Keywords: streptococcus endophthalmitis, visual outcomes, predictive factors